Epidemiological and Clinical Characteristics of COVID-19 in Children: A Systematic Review and Meta-Analysis - Li, Bingbing; Zhang, Shan; Zhang, Ruili; Chen, Xi; Wang, Yong; Zhu, Changlian (Frontiers in Pediatrics, 2020)
Given the relatively low rate and limited publicly available data regarding children with SARS-CoV-2 infection, this knowledge gap should be addressed with urgency. This systematic review with meta-analysis aimed to evaluate the epidemiological spectrum and clinical characteristics of children infected with SARS-CoV-2. Relevant international and Chinese public databases were systematically searched to identify all case studies from January 1, 2020, to May 7, 2020. This study consisted of 96 studies involving 7004 cases. The mean age of pediatric cases was 6.48 years old (95% confidence interval [CI]: 52.0–77.5), 90% had household contact, and 66% presented with mild to moderate clinical syndromes. The main symptoms were fever (47%, 95% CI: 41–53%) and cough (42%, 95% CI: 36–48%). About 23% of children were asymptomatic, 27% had comorbidity, and 29% had a co-infection. The pooled mean incubation period was 9.57 days (95% CI: 7.70–11.44). The shedding of SARS-CoV-2 in the upper respiratory tract lasted 11.43 days, and 75% of patients had virus particles in their stool. A total of 34% of the children had neutropenia and 26% had lymphocytosis. Interferon-alpha (81%) was the most commonly used antiviral drug in the children. The discharge and death rates were 79% and 1%. In conclusion, the transmissibility of pediatric COVID-19 should be not ignored due to the relatively long incubation period, shedding duration, and mild clinical syndromes.